CRITICAL ANALYSIS IN HEALTHCARE DELIVERY ADVANCEMENT THROUGH INTERDISCIPLINARY RESEARCH AND INNOVATION IN HEALTH ADMINISTRATION - 1Dhafer Saleh Mohammed Al Suwaid, 2Masoud Misfer Ali Aba Al-Harith, 3Hussain NajiAlabughbar, 4Saeed Hadhir H Alyami, 5Hussien Ali Mohammed Almohamidh, 6Saeed Mohammad Saeed Alshamlawi, 7Thamer Ahmed almakrami, 8Maiedh Saleh BureakAlsalaim, 9Noura Egall Mo; 10Mohammed Ali Mohammed Alsallum, 11Ali mohammad M Alyami, 12Sami Nasser MesferAlyami, 13Yahya mubaraknasiralsallum (Chelonian Research Foundation, 2022)
Health progress is essential to solving the global health system's complex problems. Interdisciplinary research and innovation play an indispensable role in driving this progress. This article examines the impact of research and innovation in public health management. Through a comprehensive literature review, this article explores various methods, findings, and implications of collaborative research in healthcare management. It also provides evidence, including pictures, words, and diagrams, to explain results and conclusions. The discussion delves into the implications of these advances for clinical practice and concludes with observations and recommendations for future research and practice. Keywords: Healthcare delivery, Interdisciplinary research, Innovation, Health administration, Critical analysis